Design of an efficient hybridized CS-PSO algorithm and its applications for solving constrained and bound constrained structural engineering design problems - Nirmal Kumar (Elsevier, 2021)
In the recent years, studies of structural engineering design problems are of keen interest among the researchers including engineers and algorithm developers. This article attempts to design an efficient hybridized algorithm for solving structural engineering design optimization problems. In this algorithm, after imposing some modifications on cuckoo search algorithm, the whole swarm or population is partitioned into two groups and then these are upgraded by the embedded cuckoo search (ECS) and a variant of PSO (AGQPSO) algorithms. After combining these two upgraded swarms, a deletion strategy of CS is applied with certain effective modifications. The performance of this hybridized algorithm is tested by considering six structural engineering design problems reported by several researchers and the errors made by some of them are pointed out. Finally, a comparison of the best found results and statistical analyses of this crossbred algorithm are performed with the same of existing algorithms available in the literature and it is shown that the presented algorithm performs better in almost all aspects. Also, to establish the efficiency of the proposed algorithm, convergence graphs and statistical tests are provided.